Hepatitis C virus (Flaviviridae: Hepacivirus: Hepacivirus C): regulation of signaling reactions of innate immunity - T. M. Sokolova (Вопросы вирусологии, 2021)
Studying the regulation of signaling reactions of innate immunity by the hepatitis C virus (HCV) will help to reveal the causes of the transition of the acute form of the disease to a chronic course. The molecular mechanisms of activation by HCV RNA of innate immunity receptors TLR and RLR and signal transduction processes leading to the synthesis of IFN and inflammatory cytokines are considered. The inhibitory effects of non-structural and structural HCV proteins on immune signaling reactions are analyzed in detail. The information presented is the result of an analysis of literature data published in international databases mainly over the past 5 years. In conclusion, signaling receptors are proposed as targets for the development of new antiviral drugs with immunotherapeutic activity.